Structure of the Orthoptera communities (Insecta) in an altitudinal gradient of an Andean cloud forest - SANDOVAL-MOJICA, ANDRÉS; FAGUA, GIOVANNY (Revista Colombiana de Entomología, 2006)
The variation in composition, abundance, richness, diversity and dominance of the orthopteran communities was studied along an altitudinal gradient, between 2.000 and 3.000 m, in an Andean forest at “Santuario de Flora y Fauna Guanentá Alto Río Fonce” (Santander, Colombia), from January to October of 2004. Five surveys sites were established along the length of the gradient, one every 250 m in altitude (at 2.000 m, 2.250 m, 2.500 m, 2.750 m and 3.000 m). Four 50 m x 5 m quadrants were laid out at each station where daytime manual sampling was conducted. The general sampling had a high percentage of efficiency (98.8 % ACE; 82.2 % Jackknife 1). The correspondence analysis and the similarity coefficients defined two communities: that comprised of orthopterans from the stations at 2.000 m – 2.250 m and at 2.750 m – 3.000 m, possibly due to the differences in vegetation structure and composition along the gradient. Species richness and diversity decreased directly with increasing altitude, related to the reduction in the diversity and availability of plant resource at higher elevations. Dominance increased with altitude due to a higher contribution of generalist species, probably due to greater tolerance of adverse conditions. There was no evident association between orthopteran abundance and elevation. Linear regressions to obtain values of orthopteran richness, diversity and dominance are presented.